Quantitative analysis of literature on diagnostic biomarkers of Schizophrenia: revealing research hotspots and future prospects - Liuyin Jin; Linman Wu; Jing Zhang; Wenxin Jia; Han Zhou; Shulan Jiang; Pengju Jiang; Yingfang Li; Yang Li (BMC Psychiatry)
Abstract Background Schizophrenia (SCZ) is a complex mental disorder characterized by a wide range of symptoms and cognitive impairments. The search for reliable biomarkers for SCZ has gained increasing attention in recent years, as they hold the potential to improve early diagnosis and intervention strategies. To understand the research trends and collaborations in this field, a comprehensive Bibliometric analysis of SCZ and biomarkers research was conducted. Methods A systematic search of the Web of Science Core Collection was performed to retrieve relevant articles published from January 2000 to July 2023. The search focused on SCZ and biomarkers. Bibliometric tools, including CiteSpace, VOSviewer, and R package Bibliometrix, were utilized to perform data extraction, quantitative analysis, and visualization. Results The search focused on SCZ and biomarkers, and a total of 2935 articles were included in the analysis. The analysis revealed a gradual increase in the number of publications related to SCZ and biomarkers over the years, indicating a growing research focus in this area. Collaboration and research activity were found to be concentrated in the United States and Western European countries. Among the top ten most active journals, "Schizophrenia Research" emerged as the journal with the highest number of publications and citations related to SCZ and biomarkers. Recent studies published in this journal have highlighted the potential use of facial expressions as a diagnostic biomarker for SCZ, suggesting that facial expression analysis using big data may hold promise for future diagnosis and interventions. Furthermore, the analysis of key research keywords identified inflammatory factors, DNA methylation changes, and glutamate alterations as potential biomarkers for SCZ diagnosis. Conclusion This Bibliometric analysis provides valuable insights into the current state of research on SCZ and biomarkers. The identification of reliable biomarkers for SCZ could have significant implications for early diagnosis and interventions, potentially leading to improved outcomes for individuals affected by this challenging mental disorder. Further research and collaborations in this field are encouraged to advance our understanding of SCZ and enhance diagnostic and therapeutic approaches.